Evaluation of Antioxidant, Immunomodulatory and Anticancer Properties of Methanolic Extract of Neolamarckia cadamba Linn. Fruits - Chatterjee, Amrita; Sharma, Neelima; Mazumder, Papiya Mitra (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The immune system plays an important role in various diseased conditions. Patients with compromised immune function are at increased risk of exposure. Thus, the evaluation of immunomodulatory activity of plant extracts may be helpful for prophylactic treatment approach. Objectives: The aim of present study is to evaluate the effect of methanolic extract of Neolamarckia cadamba Linn. fruits for antioxidant, immunomodulatory and anticancer properties using in-vitro and in-vitro models. Methods: In the present investigation, antioxidant property of methanolic extract of Neolamarckia cadamba fruits (NCM) was evaluated by superoxide radical and DPPH scavenging activity. The immunomodulatory property of NCM extract was analysed by determining cytokines release (IL-2 and TNFα) in murine primary thymocytes. The effects of NCM extract on humoral and cellular immunity was analysed under in vivo conditions. The anticancer activity of the extract was evaluated on Jurkat J6 cell line by MTT assay. Results: The methanolic extract of Neolamarckia cadamba fruits showed superoxide and DPPH free radical scavenging antioxidant activity and significantly increased the cytokines release (IL-2 and TNFα) in murine primary thymocytes. The increased hemagglutination antibody titre and neutrophil adhesion as well as the restoration of cyclophosphamide-induced myelosuppression and DTH response confirm the stimulatory effect of NCM on T cells. In-vitro results on Jurkat J6 cell line showed the significant increase in cell death confirming its anticancer activity. Conclusion: Thus, it can be concluded that the methanolic extract of the fruits of Neolamarckia cadamba possesses antioxidant activity, immunomodulatory property as well as anticancer potential, suggesting its therapeutic efficiency in the treatment of immune disorders as well as cancer.
Keywords: Neolamarckia cadamba; Immunomodulatory; Antioxidative; Anticancer; Cytokines; Neutrophil adhesion